Long-term clinical results on the use of platelet concentrate in the treatment of intrabony periodontal defects - BALLI, UMUT; Cetinkaya, Burcu Ozkan; Keles, Gonca Cayir; Pamuk, Ferda; Balli, UMUT; Keles, Zeynep Pinar (My University, 2014)
Objective. The purpose of this clinical investigation was to evaluate long-term results obtained with the combination of platelet pellet(PP) plus bioabsorbable barriermembrane(BM) and to compare this outcome with the results obtained using bioactive glass (BG) graft material with a BM. Materials and methods. Using a split mouth design, 11 chronic periodontitis patients (power >= at least 80%) were randomly assigned to treatment with a combination of PP/GTR or BG/GTR in contra-lateral dentition areas. Clinical attachment level (CAL) as the primary outcome variable, calculated as the sum of probing pocket depth (PPD) and gingival recession, and radiological alveolar bone level were recorded at baseline, 6 months and 5 years. Results. There were no statistical differences between test and control defects at baseline. PPD reductions and CAL and radiological alveolar bone height gains were statistically significant between baseline and 6 months and between baseline and 5 years in both groups (p= 4 mm CAL gain in both groups, while 5 year results showed that 73% of the defects attained 2 mm 0.05). No statistically significant difference in any of the clinical parameters was observed at 6 months and 5 years between the groups (p > 0.05). Conclusions. The long-term efficacy of platelet concentrate combined with a barrier membrane is similar with the combination of bioactive glass graft material and barrier membrane, suggesting that results obtained with both treatment approaches can be maintained over a period of 5 years.